Applying the principles of triage to support the rapid transition to online learning during the pandemic. Issue 6 (2nd November 2022) - Townsend, D.; Wilson, K. F.; Harvey, M.
ABSTRACT: In the higher education sector, military academies operate in environments that differ from university campuses. Like other institutions, military academies had to manage changes to learning and teaching in response to the COVID-19 pandemic. This required an approach, a model, that acknowledges and aligns with the needs of a military academy. Using a case study approach, the changes at one faculty at an Australian military academy undergoing a rapid transition to online learning are outlined and evaluated using both survey and unobtrusive data. The changes were framed by a new 3S triage model of see, solve and share, specifically designed for the context of the military academy. Distributed leadership approach and its 6E theoretical tenets are used to detail the model's application, the role of policy, and positive outcomes, including an increase in student satisfaction.